LGBTQ+ healthy ageing : how queer history impacts healthy ageing - Fox, Simon James; Hannis, Dorothy (Emerald Publishing Limited, 2024)
Populations are growing older in a public health climate where brittle public services are struggling to cope with the demands associated with ageing populations. LGBTQ+ populations also continue to grow in line with these trends but receive much less attention in the scholarly debate. This short work offers a theoretical and practical exploration of LGBTQ+ ageing in the UK, drawing on a blend of public health and occupational therapy theory, and phenomenology. Based on original primary evidence gathered through a survey and interviews, Fox and Hannis kickstart a new and much-needed discourse in the literature about hidden populations during the WHO's Decade of Healthy Ageing. Advancing the discourse on ageing by applying multiple theoretical bases to explain how minority ageing populations interact with, and are shaped by, their environments over the life course, Fox and Hannis unveil how specific social determinants over the life course impact the health outcomes and engagement with healthy ageing practices of older LGBTQ+ populations. As we navigate the intersection of queer history, public health, and ageing, LGBTQ+ Healthy Ageing serves as a vital resource for scholars, practitioners, and anyone committed to promoting healthy ageing for all.
Includes index.
Keywords: Older sexual minorities.; Family & Relationships -- Life Stages / Later Years.; Age groups: the elderly.; Relationships and families: advice and issues.; Coping with, advice about ageing.; Relating to late adulthood, old age.; elektronické knihy; electronic books